2013
DOI: 10.3892/ol.2013.1662
|View full text |Cite
|
Sign up to set email alerts
|

Effect of epidermal growth factor receptor status on the outcomes of patients with metastatic gastric cancer: A pilot study

Abstract: The expression of epidermal growth factor receptor (EGFR) has been linked to clinical outcome in several solid tumors. However, the clinical significance of EGFR (c-erbB1) in gastric cancer remains unclear. The present study was designed to detect the clinical implications of EGFR in the Turkish population. Paraffin-embedded tissue microarrays containing gastric cancer tissue were obtained from 30 patients. EGFR expression was detected using immunohistochemistry. The correlation of this biomarker to the clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 20 publications
0
11
0
2
Order By: Relevance
“…Of the HER family, EGFR expression in GC was well investigated. However, the conflicting results of EGFR expression as a prognostic marker make its detection dispensable in GC 20. Therefore, like other researchers,28 we focus this study on the expression significance of the rest of the HER members, such as HER2, HER3 and HER4.…”
Section: Discussionmentioning
confidence: 99%
“…Of the HER family, EGFR expression in GC was well investigated. However, the conflicting results of EGFR expression as a prognostic marker make its detection dispensable in GC 20. Therefore, like other researchers,28 we focus this study on the expression significance of the rest of the HER members, such as HER2, HER3 and HER4.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of a high level of EGFR has been found in various types of human cancers, including colon cancer, gastric cancer, lung cancer, breast cancer, and squamous cell carcinoma of head and neck [5], [6], [7], [8], [9], [10]. Overexpression and constitutive activation of EGFR have been associated with a poor prognosis in colon cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…[34][35][36] AKT signaling can promote tumor growth and invasion through regulation of the expression of PCNA and MMP-9. 37 Moreover, EGFR leads to the stimulation of the AKT pathway in carcinoma cells, thus enhancing their metastatic capacity. In the present study, our finding showed that knockdown of EGFR downregulated the expression of AKT, PCNA and MMP-9 and suppressed the bioactivities of GC cells, suggesting that EGFR may be involved in the development and progression of GC via AKT-mediated regulation of the PCNA and MMP-9 expression.…”
Section: Discussionmentioning
confidence: 99%